The Implementation of Outdoor Learning Strategy Focusing on Outdoor Project to Enhance Students' Ability in Writing Descriptive Text - Ratna Andina Piala; Sartin T Miolo; Titien Fatmawaty Mohammad (Jambura Journal of English Teaching and Literature, 2021)
ABSTRACT Writing is the process of expressing and developing ideas in written form. Students face some difficulties in writing descriptive text, to solve this problem the researcher tried to enhance students writing ability in descriptive text by using Outdoor Learning Strategy. Outdoor learning strategy is a strategy that use natural or environment as a place to learn and it purpose to help students can understand the material. Therefore, this study aimed to know the students improvement after got treatment of outdoor learning strategy. This research used a descriptive quantitative method, with pre – experimental design with the type one group pre – test post – test design. Population of this study is all students of class X IPA SMA Negeri 1 Suwawa and sample of this research were the students class X IPA 3. The data were collected by doing test and scoring with rubric. This research were analyzing by using t test. The result of this research shows that the mean score of pre – test is 6.84 and post – test is 14.4. Moreover, the result of hypothesis verification, it is found that T count = 74.8 at the level of significance (a = 0.05) and degree of freedom (df) = 25 – 1= 24. Then, it is found that T table= 2.064. It can be concluded that Outdoor Learning strategy can enhance students ability in writing descriptive text, because based on the criteria above shows that t count is more than t table 74.8 ≥ 2.064. Thus, it can be concluded that Outdoor Learning strategy can enhance students’ ability in writing descriptive text. Keywords: writing, descriptive text, outdoor learning strategy